PENGARUH TERAPI LINTAH TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI DI KLINIK TERAPI LINTAH MEDIS PURBA KAWEDUSAN KEBUMEN - Herlin Widaswara; Ery purwanti; Bambang Utoyo (Jurnal Ilmiah Kesehatan Keperawatan, 2012)
Hypertension is known as the silent killer because we can not find physical signs accompanying. One of the hypertension managements is the alternative treatment. Many reasons why people choose alternative medicine, such as the expensive charge of medical treatment, side effects of long-term use of chemical medicines, and medical treatment that does not reach 100 % heal especially for chronical diseases. One alternative treatment for hypertension is with leech therapy. Leech saliva contains anti-coagulant substance called hirudin that can facilitate blood flow. The aim of this study was to determine the influence of leech therapy to blood pressure of hypertension patiens in Medis Purba Leech Therapy Clinic Kawedusan-Kebumen. The method used in this study was quasi experimental with pre-test and post-test group design. There were 104 respondents taken as the sample by using accidental sampling method. The data were analyzed by paired t-test. The result showed that there are significant influence of leech therapy to blood pressure of hypertension patients in Medis Purba leech therapy clinic Kawedusan-Kebumen with p value = 0.000 that meant (P) = < 0.005. There are significant influence of leech therapy to blood pressure of hypertension patient in Medis Purba leech therapy clinic Kawedusan-Kebumen. Keywords : hypertension, leech therapy, blood pressure changes